Sakralizacja dyskursu politycznego w okresie polsko-niemieckiej rywalizacji o Górny Śląsk po I wojnie światowej (1918–1922) - Trąba, Mariusz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
A salient feature of the cultural space of Upper Silesia has always been the religion and faith of its inhabitants. During the Silesian Uprisings and the Upper Silesian plebiscite, all parties to the conflict invoked religious values in various ways. Political arguments were often presented in the form of notions, ideas or symbols derived from religious tradition.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne